New records and distribution of threatened Carabus (variolosus) nodulosus Creutzer, 1799 in Bosnia and Herzegovina (Coleoptera: Carabidae) - Kulijer, Dejan (Acta entomologica slovenica (Ljubljana), 2019)
Carabus (variolosus) nodulosus Creutzer, 1799 is a species of European conservation concern listed in the Annexes II and IV of the Habitats Directive. In Bosnia and Herzegovina (BiH) it is a rare species, up till now known mainly from historic records. In this paper the authors summarize for Bosnia and Herzegovina all the available data of C. (v.) nodulosus from literature, museum and private collections. In total, records from 19 localities are presented, including records of five new populations from central, eastern and northern part of the country. New populations were found in wet habitats along the banks of streams in deciduous and mixed forests at altitudes between 390 and 1.190 m a. An old record from Trebević Mt. at 1.600 m a. represents the highest reported altitude for the species. Considering the large number of potentially suitable habitats, especially in the northern and eastern part of BiH, it is expected to confirm a wider distribution of the species in the future. The habitat characteristics of the new finding sites are in accordance with the ecological needs of the species described in detail in literature. The distribution of the species in the West Balkan area (former Yugoslavia countries) is outlined in the paper and a short discussion on the conservation status of the species in Bosnia and Herzegovina is appended.
Keywords: Balkan; beetles; Bosna in Hercegovina; Bosnia and Herzegovina; Carabidae; Carabus; Coleoptera; Habitats Directive; Hrošči; Natura 2000